Artesunate Combined With Metformin Ameliorate on Diabetes-Induced Xerostomia by Mitigating Superior Salivatory Nucleus and Salivary Glands Injury in Type 2 Diabetic Rats via the PI3K/AKT Pathway - Zhang, Siqin; Li, Jiarui; Nong, Xiaolin; Zhan, Yuxiang; Xu, Jiazhi; Zhao, Danni; Ma, Chubin; Wang, Yuchen; Li, Yixing; Li, Zhan; Li, Jiaquan (Frontiers in Pharmacology, 2021)
Xerostomia is the most common complication that seriously affects oral health in patients with diabetes. However, to date, there is no effective treatment for diabetic xerostomia. Recent studies have reported that artesunate (ART) and metformin (Met) improve salivary gland (SG) hypofunction in murine Sjögren's syndrome. Therefore, aim of this study was to investigate the effect and underlying mechanism of artesunate (ART) alone and in combination with metformin (Met) on hyposalivation in type 2 diabetes mellitus (T2DM) rats. T2DM rats were induced using a high-fat diet and streptozotocin. SPF male Sprague–Dawley (SD) rat were divided into the following five groups: normal control group, untreated diabetic group, ART-treated diabetic group (50 mg/kg), Met-treated diabetic group (150 mg/kg), and ART/Met co-treated diabetic group (50 mg/kg ART and 150 mg/kg Met). ART and Met were intragastrically administered daily for four weeks. The general conditions, diabetes parameters and serum lipids were evaluated after drug treatment. Furthermore, we observed changes in the central superior salivatory nucleus (SSN) and peripheral SG, and changes in the expressions of aquaporin 5 (AQP5), acetylcholinesterase (AchE), brain-derived neurotrophic factor (BDNF), and PI3K/AKT pathway- (AKT, PI3K, p-AKT, and p-PI3K), apoptosis- (Bax, Bcl-2, and Caspase3), and autophagy- (LC3 and P62) related markers in T2DM rats after treatment.The diabetic rats showed hyposalivation, weight loss, increased urine volume and water consumption, hyperglycemia, insulin resistance, glucose intolerance, dyslipidemia, pancreatic injury, SSN damage, and SG lesion. However, the ART/Met combination therapy exhibited better improvement in mitigating these pathological consequences than ART or Met alone. Furthermore, the expression of AKT, PI3K, p-AKT, p-PI3K, Bcl-2, P62, AQP5, AchE, and BDNF in SGs was significantly enhanced after ART/Met combination treatment, whereas the expression of Bax, Caspase3, and LCII/LCI was significantly reduced compared to the untreated diabetic rats. This suggests that ART/Met combination therapy ameliorated diabetes-induced SG dysfunction through activating the PI3K/AKT pathway to inhibit apoptosis and autophagy. These results demonstrated that ART/Met combination treatment exhibited a synergistic effect on alleviating diabetes-induced xerostomia via improving SG and SSN damage in hyperglycemia to increase AQP5, AchE, and BDNF expression in SG. These findings might provide a novel treatment strategy for diabetes-induced xerostomia.